Optimalisasi Kerjasama Perdagangan Indonesia dengan Negara Mitra di Masa Pandemi Covid-19 - Paryadi, Deky (Global and Policy Journal of International Relations, 2021)
Abstract Globalization encourages every country to move to develop innovation. The emergence of globalization certainly has an impact on the life of a country, including Indonesia. Diversification and expansion of exports to non-traditional countries in accordance with the policy direction of Indonesia's international trade cooperation. The expansion of exports to non-traditional markets is one of the strategies undertaken by the Government to anticipate the current global trade conditions, this condition provides an opportunity for Indonesia to open up greater market access and rise faster during this pandemic. This analysis aims to see the effectiveness of international trade cooperation during the COVID-19 pandemic. The research method used are desk research and comparison study, by comparing Indonesia's trade with partner countries that have and have not conducted trade cooperation. Use secondary trade data from the Central Bureau of Statistics before and during the pandemic. Based on this analysis, there are indications that the cooperation carried out by partner countries that have been explored cannot run optimally by looking at the structure of trade value as well as the growth of exports and imports of Indonesia with partner countries. Keywords: International Trade Cooperation, Pandemic Covid 19, Export ImportGlobalisasi mendorong setiap negara untuk bergerak mengembangkan inovasi. Munculnya globalisasi tentunya membawa dampak bagi kehidupan suatu negara termasuk Indonesia. Diversifikasi dan perluasan ekspor ke negara non tradisional sesuai dengan arah kebijakan kerjasama perdagangan internasional Indonesia. Perluasan ekspor ke pasar non tradisional tersebut merupakan salah satu strategi yang dilakukan Pemerintah guna mengantisipasi kondisi perdagangan global saat ini, kondisi ini memberikan kesempatan Indonesia untuk membuka akses pasar yang lebih besar serta bangkit lebih cepat di masa pandemi ini. Analisis ini bertujuan untuk melihat efektivitas kerjasama perdagangan internasional dimasa pandemi covid 19. Metode penelitian yang akan digunakan adalah comparison studydan desk research, dengan membandingkan kerjasama Inonesia dengan negara lain tanpa adanya perjanjian perdagangan. Data perdagangan menggunakan sekunder dari Badan Pusat Statistik sebelum dan saat pandemi. Berdasarkan analisis ini terdapat indikasi bahwa kerjasama yang dilakukan oleh negara mitra yang sudah dijajaki tidak dapat berjalan optimal dengan dengan melihat struktur nilai perdagangan serta pertumbuhan ekspor dan impor Indonesia dengan negara mitra. Kata kunci: Kerjasama Perdagangan Internasional, Pandemic Covid 19, Ekspor Impor  DOI : https://doi.org/10.33005/jgp.v9i2.3008